2007
DOI: 10.3168/jds.s0022-0302(07)71579-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bovine Immunoglobulins Resistant to Peptic Digestion: New Perspectives in the Prevention of Failure in Passive Immunization of Neonatal Calves

Abstract: In calves, neonatal mortality and disease susceptibility are greatly influenced by failure in passive immunization, normally provided by colostrum ingestion just after birth. Formulations projected to replace natural colostrum have not been successful, and one of the possible reasons for such failure is that orally administered Ig are probably digested in the gastrointestinal tract, so they are not absorbed as intact functional molecules. With the aim of finding an adequate colostrum substitute, we used column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…These include traditional methods of ammonium sulfate precipitation and column chromatography [3,5,145,184]. Affinity chromatographic methods used to isolate IgG include lectins [185]; protein A or G chromatography [186,187], and more recently, isolation with protein A/G immobilized electrospun polyethersulfone membranes [188]; metal chelate chromatography [189,190]; and adsorption with polyanhydride microparticles [191]. The range of detection and quantification methods for IgG, most often analyzed by radial-immunodiffusion [192] or enzyme-linked immunosorbant methods [193], are now expanding to include methods that detect multiple proteins, such as thermally addressed immunosorbant assays [194], and rapid methods that may be integrated into milking systems, such as surface plasmon resonance-based immunosensors [195].…”
Section: Immunoglobulin Isolation and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These include traditional methods of ammonium sulfate precipitation and column chromatography [3,5,145,184]. Affinity chromatographic methods used to isolate IgG include lectins [185]; protein A or G chromatography [186,187], and more recently, isolation with protein A/G immobilized electrospun polyethersulfone membranes [188]; metal chelate chromatography [189,190]; and adsorption with polyanhydride microparticles [191]. The range of detection and quantification methods for IgG, most often analyzed by radial-immunodiffusion [192] or enzyme-linked immunosorbant methods [193], are now expanding to include methods that detect multiple proteins, such as thermally addressed immunosorbant assays [194], and rapid methods that may be integrated into milking systems, such as surface plasmon resonance-based immunosensors [195].…”
Section: Immunoglobulin Isolation and Stabilitymentioning
confidence: 99%
“…In adults ingesting bovine anti- Clostridium difficile immunoglobulins, toxin-neutralizing activity paralleled the bovine IgG content in ileal effluent [205], and in stool samples [204]. A pepsin-resistant form of bovine IgG representing approximately 10% of colostral immunoglobulin has been isolated with a lectin that binds O -linked oligosaccharides [185], indicating that some proportion of IgG in the gastrointestinal tract may remain intact.…”
Section: Immunoglobulin Isolation and Stabilitymentioning
confidence: 99%
“…Es necesaria la realización del secuenciamiento nucleotídico de los productos del RT-PCR tiempo real para identificar tales variaciones y emplear técnicas avanzadas para develar las implicancias de tales cambios y sus efectos sobre los individuos en caso se presenten. Los resultados obtenidos con el RT-PCR en tiempo real, usando oligonucleótidos diseñados para el ARNm de la IgA, permitieron establecer que los animales neonatos aparentemente sanos que no habían tomado calostro no tienen presencia detectable de ARNm de IgA en la mucosa intestinal, siendo la producción detectable a partir del primer día de edad tras el consumo de calostro, debido a que la producción de IgA es dependiente del estimulo antigénico que está comenzando a presentarse con la colonización de microorganismos a nivel intestinal y también a las moléculas inductoras / reguladores de la respuesta inmune presente en el calostro y leche (Porto et al, 2007). Asimismo, al 25 % de las muestras de animales sanos de diferentes edades no se les detectó el ARNm de IgA, esto puede ser debido a diversos eventos.…”
Section: Discussionunclassified
“…En segundo lugar podría existir un número de animales inmunodeficientes que no puedan expresar la IgA, enfermedad denominada "deficiencia selectiva de IgA", que se presentan en ARNm de IgA podrían estar asociadas a la presencia de moléculas inmunomoduladoras en calostro y leche junto con la estimulación de los antígenos de la microbiota que se está implantando durante este período a partir de la ingesta del alimento materno y posteriormente pasto natural (Porto et al, 2007). El intestino es el lugar del organismo donde desde el momento del nacimiento existe el mayor y más constante estímulo antigénico por el continuo contacto con los antígenos alimentarios y los elementos de la flora intestinal normal (Strobel y Mowat, 1998).…”
Section: Discussionunclassified
“…Studies on the structure-function relationship of the glycoproteins have shown that the carbohydrate part of a glycoprotein confers important and specific biological roles: immunogenicity [7,8], solubility [9], recognition [10], protection from proteolytic attack [11], induction and maintenance of the protein conformation in a biologically active form [12,13]. In really, there are four major ways in which glycosylation affects the structure or function of a protein.…”
Section: Protein Glycosylationmentioning
confidence: 99%